Effect of carnitine, methionine, vitamins E and B12, selenium, and zinc as components of a complex preparation on the immune status of rats under conditions of toxic liver injury - Vus, U. M.; Gutyj, B. V.; Koropetska, N. Y.; Brygadyrenko, V. V.; Vasiv, R. O. (Regulatory Mechanisms in Biosystems, 2026)
Toxic liver injury is accompanied by the development of oxidative stress and disturbances in the functional state of the immune system, particularly in the parameters of nonspecific resistance. The use of complex preparations with antioxidant and immunomodulatory properties is considered a promising approach for correcting such disorders. The aim of this study was to investigate the effect of a complex preparation containing carnitine, vitamins E and B 12 , methionine, selenium, and zinc on the antioxidant and immune status of rats under conditions of toxic liver injury induced by carbon tetrachloride. The experiment was carried out on adult male Wistar rats weighing 180–200 g, which were divided into three groups: control, experimental (carbon tetrachloride-induced injury), and experimental with correction using the preparation “Devivit Carnitine”. Toxic liver injury was induced by intramuscular administration of a 50% oil solution of carbon tetrachloride at a dose of 0.25 mL/100 g body weight on days 1 and 3. The preparation was administered at a dose of 0.1 mL/kg body weight for 5 days. Blood samples were collected on days 2, 5, 10, and 14 of the experiment. Lysozyme and bactericidal activity of blood serum, the level of circulating immune complexes, and phagocytic activity of neutrophils were determined. It was found that administration of carbon tetrachloride caused pronounced changes in the immune status of rats, manifested by increased lysozyme and bactericidal activity of blood serum and elevated levels of circulating immune complexes at early stages of the experiment, followed by suppression of both humoral and cellular components of nonspecific resistance. The use of the preparation “Devivit Carnitine” contributed to normalization of immune parameters, which was expressed by increased antimicrobial activity of blood serum, reduced levels of circulating immune complexes, and restoration of phagocytic activity of neutrophils. Carbon tetrachloride-induced liver injury is accompanied by the development of oxidative stress and immune imbalance. The complex preparation “Devivit Carnitine” exhibits pronounced antioxidant and immunomodulatory properties, contributing to the restoration of nonspecific resistance in rats. Further studies are warranted to elucidate the molecular mechanisms of action of the preparation components, particularly their effects on the antioxidant defense system. It is also advisable to investigate the efficacy of the preparation under different models of hepat o toxicity, as well as in productive animals to substantiate its practical application in veterinary medicine.